Escitalopram population pharmacokinetics in people living with human immunodeficiency virus and in the psychiatric population: Drug–drug interactions and probability of target attainment. Issue 9 (7th July 2019) - Courlet, Perrine; Guidi, Monia; Glatard, Anaïs; Alves Saldanha, Susana; Cavassini, Matthias; Buclin, Thierry; Marzolini, Catia; Eap, Chin B.; Decosterd, Laurent A.; Csajka, Chantal
Abstract : Aims: The aims of this study were to characterize escitalopram pharmacokinetic profile, to identify factors influencing drug exposure, notably drug–drug interactions with antiretrovirals, and to simulate expected exposure under standard dosage regimen. Methods: A population pharmacokinetic analysis was performed using NONMEM. A total of 159 plasma concentration measurements were obtained from 39 human immunodeficiency virus (HIV)‐infected and 71 uninfected psychiatric patients. The influence of age, weight, sex, HIV and psychiatric cohorts, racemic citalopram treatment, and comedications on oral clearance was examined. Simulations served to calculate the percentage of patients expected to be under‐ or over‐exposed, considering established therapeutic targets (15–80 ng/mL). Results: A 1‐compartment model with first‐order absorption and elimination described the data adequately. The average escitalopram clearance and volume of distribution were 23.1 L/h (interindividual variability 51%), and 920 L, respectively. Escitalopram disposition did not differ between HIV‐infected and uninfected patients, and was not affected by antiretroviral treatments. Coadministration of at least 1 proton‐pump inhibitor (CYP2C19 inhibitor) modestly influenced escitalopram elimination (clearance decreased by 19%), with limited clinical relevance. Model‐based simulations showed that, under a standard regimen of 10 mg once daily, a significant proportion of patients (56%) might be under‐exposed. Conclusion: The variability in escitalopram disposition is large and poorly explained by demographic, clinical and environmental covariates, thus suggesting a role for dosage individualization based on therapeutic drug monitoring in case of poor clinical response. Escitalopram disposition is modestly impacted by comedications and therefore no a priori dosage adjustments are needed in patients receiving antiretroviral treatments, including boosted regimens.